The Library of Rudolf Steiner: The Books in English - Paull, John (Journal of Social and Development Sciences, 2018)
The New Age philosopher, Rudolf Steiner (1861-1925), was the most prolific and arguably the most influential philosopher of his era. He assembled a substantial library, of approximately 9,000 items, which has been preserved intact since his death. Most of Rudolf Steinerâ€™s books are in German, his native language however there are books in other languages, including English, French, Italian, Swedish, Sanskrit and Latin. His library hosts more books in English than in any other foreign language. Steiner esteemed English as â€œa universal world languageâ€. The present paper identifies 327 books in English in Rudolf Steinerâ€™s personal library. Fifty percent of the English-language books identified are categorized as Theosophy (n=164). Rudolf Steiner was the General Secretary of the German branch of the Theosophy Society from 1902, and he hived off his own Anthroposophy Society in 1912. The present study reveals that Steiner maintained his interest in theosophy throughout his life as he stayed up to date with the proliferating portfolio of Theosophy publications. The publication dates of Steinerâ€™s Theosophy collection range from 1877 to 1923. The leading exponents of Theosophy in his day are well represented in Steinerâ€™s collection, including Annie Besant (n=61), Charles Lead beater (n=13), William Westcott (n=13) and Helena Blavatsky (n=10). Of the other 50% of the Anglo-books identified, 20% are in the category of Religion (n=67), 10% are Social Science (n=33), 6% are Philosophy (n=21), 4% are Science (n=13), and 3% each are Anthroposophy (n=11), History (n=9) and Arts (n=9). The publication dates of Steinerâ€™s Anglo-books span the period 1659 to 1925. This demonstrates that Steiner was acquiring Anglo-books right to the end of his life. Steinerâ€™s library throws light on the development of the thoughts of this remarkable individual and the present paper reveals Steinerâ€™s engagement throughout his life with the world of Anglo-publishing and thought.